Impact of Microcredit Scheme on the Development of Entrepreneurship Skills among Low Income Households in a Developing Country Context - Manaf, Halimah Abdul (International Journal of Economics and Financial Issues, 2017)
This study seeks to investigate the extent to which microcredit scheme can predict the development of entrepreneurship skills, particularly on entrepreneurial acumen, competitive of business, advantages of small business and business survival. This quantitative study is based on survey data from 1176 microcredit scheme participants. The data shows that participant involvement in microcredit scheme has a positive relationship with the development of entrepreneurial skills. The study provides insight into how theories from microcredit scheme may help us to understand the nature of entrepreneurial development, particularly among low income households. This article has focused only on the borrowers from microcredit scheme known as AIM and TEKUN. Hence, future research is recommended to include leadership style and expand the sample of the research to the elite group consisting of chairman/CEO of these two institutions. Emergent results make a contribution to research regarding how microcredit scheme can lead to the development of entrepreneurial skills in the context of developing countries. The findings demonstrate that to sustain in small medium scale business are require essential entrepreneurship skills such as competitive advantage, business survival to try varies type of business before they can be succeeding. Keywords: Microcredit, Entrepreneurship Development Skills, Malaysia JEL Classification: ZOO